Mixed germ cell tumor of mediastinum/lung masquerading as hemangioma in fine needle biopsy - Rathna Nuti; Surender Bodhireddy; Seshadri Thirumala (Wolters Kluwer Medknow Publications, 2013)
The histological predominance of one component in a germ cell tumor can lead to a mistaken diagnosis. Here, we describe a mediastinal teratoma with predominant vascular proliferation (>90%) which on fine needle biopsy was diagnosed as a pulmonary hemangioma. Later, resection specimen revealed other components constituting ~4%, changing the diagnosis while illustrating theimportance of careful evaluation. A 37-year-old Caucasian male with shortness of breath, weight loss, and history of recently resolved pneumonia was diagnosed with hemangioma, after a computed tomography guided fine needle biopsy of a -16.3-cm mediastinal pulmonary mass revealed abundant benign vascular elements. Following tumor excision, ~94% of the sample exhibited predominant vascular elementsThe mass also exhibited rare focal areas of malignant epithelium in a reticular arrangement and undifferentiated pleomorphic cells associated with vascular invasion. These atypical epithelial cells were positive for CD30, pan CK, AFP, β-HCG and CD 117, thusprocuring a diagnosis of mediastinal mixed germ cell tumor. Although mixed germ cell tumors consist of various tissue types, diagnosis can be easily overlooked if one component dominates. Therefore, obtaining adequate representative neoplasm samples, and sectioning the samples thoroughly, searching for coexisting tissue types is critical for accurate diagnosis.